(untitled) (Research, Society and Development, 2020)
Introduction: Communicable infectious diseases are caused by micro-organisms that need a reservoir, being the main cause of death in the 1930s, accounting for 45.7% of deaths in Brazil. However, this index decreased due to changes in the health sector, epidemiological surveillannce and research institutes. Health professionals are responsible for diagnosis and treatment, thus, susceptible to developing these infections, seuch as occupational accidents, being able to prevent them through the use of personal protective equipment (PPE). Objective: To investigate through a literature review the use of PPE and the importance of PPE by health professionals in the face of communicable infectious diseases. Methods: This is na integrative review carried out on the SciELO and VHL electronic databases. Result: 54 qualitative, quantitative and mixed articles were selected based on the inclusion and exclusion criteria, which served as a basis for collecting relevant information, in addition to being tabulated and exposed. Final considerations: The use of PPE by health workers is not yet a reality, due to the rates of occupational accidents abserved, especially among nursing professionals and technicians. In addtion, hygiene measures, such as hand washing, are often not adopted, even though they are na important measure for the elimination of biological fluids after exposure. Thus, it is necessary to adopt continuing education by the institutions to maintain the practice of using PPE in daily life, as well as providing resources and adequate infrastructure for the adoption of these measures.